The mechanisms of natural products for eye disorders by targeting mitochondrial dysfunction - Sun, Gui-Feng; Qu, Xin-Hui; Jiang, Li-Ping; Chen, Zhi-Ping; Wang, Tao; Han, Xiao-Jian (Frontiers in Pharmacology, 2024)
The human eye is susceptible to various disorders that affect its structure or function, including glaucoma, age-related macular degeneration (AMD) and diabetic retinopathy (DR). Mitochondrial dysfunction has been identified as a critical factor in the pathogenesis and progression of eye disorders, making it a potential therapeutic target in the clinic. Natural products have been used in traditional medicine for centuries and continue to play a significant role in modern drug development and clinical therapeutics.Recently, there has been a surge in research exploring the efficacy of natural products in treating eye disorders and their underlying physiological mechanisms. This review aims to discuss the involvement of mitochondrial dysfunction in eye disorders and summarize the recent advances in the application of natural products targeting mitochondria. In addition, we describe the future perspective and challenges in the development of mitochondria-targeting natural products.